Military green technology: present and future - Miličević, Zoran M.; Bojković, Zoran S. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: This paper aims to present military green technology through present concepts, solutions and challenges, as well as through future trends, particularly in wireless communication.Methods: Analyses and syntheses were used to consider various aspects, challenges and developments of military green technology.Results: Important aspects of organization, challenges and strategies in military green technologies are presented. Next, the role of a green energy action plan is emphasized. Furthermore, green defence solutions and security challenges are considered. Besides presenting green technologies of today, primarily focused on wireless networks, especially 5G, the paper also considers the impact of biofuels, methanol-based fuel cells, hydrogen fuel cells, hybrid electrical vehicles and photovoltaic energy. Finally, green technologies for the future are presented through some of the most important technologies: next generation wireless networks, pulse detonation engines, piezoelectricity, and biodegradable platforms.Conclusion: Military green technology is now necessary for approaching wireless networking in order to meet challenges of high demands of wireless traffic and energy consumption. Also, military green technology will require further constant considerations in the field of efficiency and sustainability of application as well as research to provide different acceptable solutions, not only in technical, but also in the organizational domain, in order to be applied in military environment.
Keywords: wireless networks; methanol-based fuel cells; hydrogen fuel cells; photovoltaic energy; pulse detonation engines; biodegradable platform